Swimming Upstream: Navigating ethical practices in the creation of a participatory youth media workshop - Margolin, Myra (Les ateliers de l'éthique / The Ethics Forum, 2009)
Despite the growing popularity of participatory video as a tool for facilitating youth empowerment, the methodology and impacts of the practice are extremely understudied. This paper describes a study design created to examine youth media methodology and the ethical dilemmas that arose in its attempted implementation. Specifically, elements that added “rigor” to the study (i.e., randomization, pre- and post-measures, and an intensive interview) conflicted with the fundamental tenets of youth participation. The paper concludes with suggestions for studying participatory media methodologies that are more in line with an ethics of participation.